A comparative analysis between ring annuloplasty and de vega annuloplasty in functional tricuspid regurgitation - Bhagwan, Jai; Guha, Soumya; Gupta, Anubhav; Padhy, Ajit Kumar; Grover, Vijay; Gupta, Vijay Kumar (International Surgery Journal, 2018)
Background: Tricuspid valve disease frequently accompanies left side valve disease. Surgical correction of significant functional TR at the time of left side valve surgery is recommended. The current study was under taken to assess the early impact of ring annuloplasty and De Vega annuloplasty techniques in functional significant TR in a predominantly rheumatic population. Methods: Between January 2010 and January 2014, a total 80 patients underwent surgery for functional tricuspid valve disease. Retrospective data analysis was done. The patient selection criteria were as per the institutional protocol (for all functional severe TR and moderate TR with Tricuspid Index > 21mm/m2) based on preoperative TTE (Trans-thoracic Echocardiography) findings and the type of procedure was the surgeon’s decision on table. Techniques routinely involved in the repair procedures included tricuspid prosthetic ring Annuloplasty (MC3) and De Vega suture annuloplasty. Postoperatively all the patient had routine TTE before hospital discharge (considered as immediate post op period). Follow up was present till 6 months post-operatively (in the form of another TTE and clinical data sheet) at the time of data collection for this study. Results: There was no statistically significant difference in residual significant TR when ring annuloplasty was compared to De Vega repair. There was significant improvement in NYHA status after both ring and De Vega annuloplasty. Conclusions: Present study shows similar results with both the techniques of TV repair when applied to functionally significant TR in a pre-dominantly rheumatic population.